'A man of curious enquiry': John Peyton's Grand Tour to central Europe and Robert Cecil's intelligence network, 1596–1601. Issue 3 (20th October 2014) - Sobecki, Sebastian
Abstract : Between 1596 and 1601 John Peyton the Younger (1579–1635) travelled to Germany, Bohemia, Poland–Lithuania, Switzerland, and Italy. His accounts of the Empire and Bohemia are among the most detailed and best informed reports to have survived from the period, yet they are virtually unknown to modern scholarship. Furthermore, he was the author of the celebrated description of the Polish–Lithuanian Commonwealth, A Relation of the State of Polonia and the United Provinces of that Crown, Anno 1598. Based on new evidence, this article shows that John Peyton's travels in Central Europe formed part of Cecil's attempts to gather intelligence on Spanish diplomatic activity in the Empire and in the Polish–Lithuanian Commonwealth. I argue that Peyton was one of many contemporaries who left England on an Elizabethan Grand Tour; a peculiar mixture of visiting European countries for culture, education and intelligence. His writings, however, belong to the more sophisticated written achievements in Elizabethan intelligence gathering.